2006
DOI: 10.1542/peds.2005-1465
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Central Venous Catheters Used for the Treatment of Acute Hematogenous Osteomyelitis

Abstract: Interventions to reduce CVC-associated complications should be developed and evaluated, particularly for young children and those from families with low household incomes. Clinical trials are needed to evaluate the safety and efficacy of oral antibiotic therapy after a short course of IV therapy as an alternative to prolonged IV therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 24 publications
4
54
1
1
Order By: Relevance
“…Its good oral absorption makes it an important option in the therapy of the outpatients or as a follow up after an intravenous (IV) therapy (de-escalation). This permits an early transition to the outpatient management of the susceptible infections without the complications of a continued IV access [18]. It is effective against both the methicillin resistant and the methicillin sensitive Staphylococcal infections [1].…”
Section: Discussionmentioning
confidence: 99%
“…Its good oral absorption makes it an important option in the therapy of the outpatients or as a follow up after an intravenous (IV) therapy (de-escalation). This permits an early transition to the outpatient management of the susceptible infections without the complications of a continued IV access [18]. It is effective against both the methicillin resistant and the methicillin sensitive Staphylococcal infections [1].…”
Section: Discussionmentioning
confidence: 99%
“…An early switch to oral therapy is particularly important for children, as the risk for central line-related complications is high. Ruebner et al found that of 75 patients who received Ͼ2 weeks of treatment for acute OM through a central venous catheter (CVC), 41% developed at least one CVC-related complication (515).…”
Section: Osteoarticular Infections In Childrenmentioning
confidence: 99%
“…Central venous lines or PICCs and OPAT has attendant risks, with 3-11% of central venous line-associated infection noted in the USA. 57,58 Additional or second-line antibiotics for complex disease or where resistant pathogens are identified…”
Section: Continuation Of Intravenous Antibiotics For More Than 2 Weeksmentioning
confidence: 99%